2018
DOI: 10.1186/s13104-018-3900-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete blood count data and leukocyte expression of cytokine genes and cytokine receptor genes associated with bovine respiratory disease in calves

Abstract: ObjectiveThe purpose of this study was to evaluate potential relationships between cytokine gene expression, complete blood counts (CBC) and animals that were sick or would become sick. The CBC and the transcript abundance of cytokines and their receptors expressed in leukocytes were measured from calves at two early timepoints, and again after diagnosis with bovine respiratory disease (BRD).ResultsBlood was collected from calves at pre-conditioning (n = 796) and weaning (n = 791) for CBC. Blood counts were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
5
13
0
Order By: Relevance
“…This could indicate that not only lung consolidation but clinical disease symptoms are necessary to detect differences in neutrophil number. The neutrophil and N:L profiles are in agreement with previous studies, where higher values have been reported in calves affected by BRD compared to healthy calves (Burciaga-Robles et al, 2010;Lindholm-Perry et al, 2018). Previous authors reported low eosinophil and high RBC numbers in blood samples at arrival to facilities as indicators of calves at a greater risk of developing clinical signs of BRD (Richeson et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…This could indicate that not only lung consolidation but clinical disease symptoms are necessary to detect differences in neutrophil number. The neutrophil and N:L profiles are in agreement with previous studies, where higher values have been reported in calves affected by BRD compared to healthy calves (Burciaga-Robles et al, 2010;Lindholm-Perry et al, 2018). Previous authors reported low eosinophil and high RBC numbers in blood samples at arrival to facilities as indicators of calves at a greater risk of developing clinical signs of BRD (Richeson et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…The blood chemistry values were in the normal range for calves ( 47 , 48 ). Only glucose showed a slight reduction in animals supplemented with herbal choline.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, these studies have collected these fluids and tissues at postmortem examination. Only a few studies ( Lindholm-Perry et al, 2018 ; Scott et al, 2020 ) use RNA extracted from blood for gene expression analysis despite the relative ease of its sampling from live animals. We therefore applied a functional genomics approach to investigate changes in the whole-blood transcriptome, making two different comparisons; the first examined the difference in gene expression between all the BRD and NB animals, while the second explored the larger variation observed among the BRD animals.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis can lead to insights into disease processes, and biomarkers to assess disease states, progression, and prognosis. Thus far, transcriptomic techniques have examined bronchoalveolar fluids, lung tissue, and sputum samples of cattle with or without BRD ( Aich et al, 2009 ; Rai et al, 2015 ; Behura et al, 2017 ; Johnston et al, 2019 ), but there is much less information on the whole-blood transcriptome ( Lindholm-Perry et al, 2018 ; Sun et al, 2020 ). In comparison with lung tissue biopsies, blood is easier to obtain and can be collected repeatedly throughout the production period and can give real-time results, instead of postmortem conclusions.…”
Section: Introductionmentioning
confidence: 99%